ESTABLISHMENT OF AWARDS NAMED AFTER HISTORICAL FIGURES IN UZBEKISTAN: AWARDING PROCESSES - Karimjonov J. M. (TARIXIY TADQIQOTLAR, 2025)
This article examines the awards established in the name of historical figures who played an important role in the history of Uzbekistan, the awarding process, and its specific aspects. It also analyzes the award symbols, types of awards, statistics of awardees, and the legal basis for awarding.